Project Management Handbook - Kuster, J (Springer, 2015)
This practical handbook offers a comprehensive guide to efficient project management. It pursues a broad, well-structured approach, suitable for most projects, and allows newcomers, experienced project managers and decision-makers to find valuable input that matches their specific needs. The Project Management Compass guides readers through various sections of the book; templates and checklists offer additional support. The handbook’s innovative structure combines concepts from systems engineering, management psychology, and process dynamics. This international edition will allow to share the authors' experience gained in many years of project work and over 2,000 project management and leadership seminars conducted for BWI Management Education in Zurich, Switzerland.